When Was the Pythian Nome Performed? - Almazova, Nina (Hyperboreus, 2015)
According to Strabo, the Pythian nome, which depicted Apollo’s victory over Python, formed the program of auletic and citharistic contests from their introduction at the Pythian Games (586 and 558 BC respectively). Yet interpreting any solo Pythian victory as proof of performing a Pythian nome is unfounded. The existence of the vocal, citharodic Pythian nome is not well evidenced. For instrumentalists it was likely only obligatory at the beginning. In 12 of 17 known cases we are not aware what the Pythian winners played, and in two cases (in the early 5th and in the 4th century BC) other nomes were performed at the Pythian contests. A hypothesis that the program was divided into compulsory and optional cannot be proven; rather an agonistic occasion stimulated gradual loss of ritual character of the pieces performed and the acquiring of more variety, whereas musical representation of a dragon-ﬁght was probably transferred from the agonistic to the cult program of the festival. References to the Pythian nome are scarce; the latest of what may be considered as evidence on its performance concerns the 4th cent. BC and indicates non-agonistic occasions. Using πυθικός as a technical term meaning ‘soloistic’, which is typical of the Roman period, does not imply playing a Pythian nome; even at the point at which this terminology was ﬁrst established it referred more likely to the Pythian Games in general. In Roman times, the scarcity of evidence (even though Pythian victories remained prestigious and were sought for) and discordant word usage of the authors show that the Pythian nome no longer existed.